The book club hotel - Morgan, Sarah (Romance fiction writer) (Canary Street Press, 2023)
"With its historic charm and picture-perfect library, the Maple Sugar Inn is considered the winter destination. As the holidays approach, the inn is fully booked with guests looking for their dream vacation. But widowed far too young, and exhausted from juggling the hotel with being a dedicated single mom, Hattie Coleman dreams only of making it through the festive season. But when Erica, Claudia and Anna--lifelong friends who seem to have it all--check in for a girlfriends' book club holiday, it changes everything. Their close friendship and shared love of books have carried them through life's ups and downs. But Hattie can see they're also packing some major emotional baggage, and nothing prepares her for how deeply her own story is about to become entwined in theirs. In the span of a week over the most enchanting time of the year, can these four women come together to improve each other's lives and make this the start of a whole new chapter?"--